Systemic sclerosis complicated with renal thrombotic microangiopathy: a case report and literature review - Weiwei Kong; Yaomin Wang; Huiping Wang; Qin Zhou; Jianghua Chen; Fei Han (BMC Nephrology, 2022)
Abstract Background Systemic sclerosis (SSc) may overlap with other connective tissue diseases, which is named overlap syndrome. Scleroderma renal crisis (SRC) is a rare but severe complication of SSc. SSc related thrombotic microangiopathy (SSc-TMA) is an infrequent pathology type of SRC, while SSc-TMA accompanied by overlap syndrome is very rare. Case presentation This study reported a case of acute kidney injury (AKI) accompanied with overlap syndrome of SSc, systemic lupus erythematosus (SLE) and polymyositis (PM). The renal pathology supported the diagnosis of SSc-TMA but not SLE or PM-related renal injury, characterized by renal arteriolar thrombosis, endothelial cells edema, little cast in tubules and mild immune complex deposition. The primary TMA related factors (ADAMTS13 and complement H factor) were normal. Thus, this case was diagnosed as secondary TMA associated with SSc. The patient was treated with renin angiotensin system inhibitors, sildenafil, supportive plasma exchange/dialysis, and rituximab combined with glucocorticoids. After 2 months of peritoneal dialysis treatment, her renal function recovered and dialysis was stopped. Conclusion This study presented a case of SSc-TMA with overlap syndrome. Rituximab can be used as a treatment option in patients with high SRC risk or already manifesting SRC.